2004
DOI: 10.1207/s15327914nc4801_2
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling and Genetic Alterations of the Selenoproteins GI-GPx and SePP in Colorectal Carcinogenesis

Abstract: The trace element selenium is discussed as a chemopreventive agent in colorectal carcinogenesis. Selenocysteine-containing proteins, so-called selenoproteins, represent potential molecular targets for nutritive selenium supplementation. Due to their antioxidative potential, the selenoproteins gastrointestinal glutathione peroxidase (GI-GPx) and selenoprotein P (SePP) are considered to provide protection against reactive oxygen species (ROS), thereby reducing DNA damage and preventing development of colon cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 33 publications
6
78
1
2
Order By: Relevance
“…SEPP1 contains 10 selenocysteines and is the only selenoprotein with more than one selenocysteine. SEPP1 binds f40% to 60% of the selenium in plasma and is found in several tissues, including the colon, where it becomes down-regulated during tumor development (26,(47)(48)(49). SEPP1 has three important functions: transport of selenium to target tissues, intracellular selenium binding and supply, and protection against oxidative stress (47,(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…SEPP1 contains 10 selenocysteines and is the only selenoprotein with more than one selenocysteine. SEPP1 binds f40% to 60% of the selenium in plasma and is found in several tissues, including the colon, where it becomes down-regulated during tumor development (26,(47)(48)(49). SEPP1 has three important functions: transport of selenium to target tissues, intracellular selenium binding and supply, and protection against oxidative stress (47,(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium has been identifact that, even under conditions of severe selenium deficiency, its production perseveres (19). Previous studies have shown that SEPP1 is downregulated in colorectal cancers (CRCs) (21) and SNPs within the gene are associated with advanced adenoma risk (22). Because SEPP1 serves as the major selenium transport protein, the known effects of selenium on WNT and NRF2 signaling in target tissues may partially depend on SEPP1.…”
Section: Introductionmentioning
confidence: 99%
“…4 Supplementation with Se has also been shown to resist and reduce the carcinogenic effects of mutagens and carcinogens. 7 It can also block pre-cancerous lesions, 8 and Se supplementation has been reported to increase natural killer cell counts before surgical operation. 9 The level of SelP expression in gastric mucosa infected by Helicobacter pylori correlated negatively with expression of proliferating cell nuclear antigen, but correlated positively with expression of P16.…”
Section: Discussionmentioning
confidence: 99%